How Does Exercise Improve Implicit Emotion Regulation Ability: Preliminary Evidence of Mind-Body Exercise Intervention Combined With Aerobic Jogging and Mindfulness-Based Yoga - Zhang, Yifan; Fu, RuoFan; Sun, Li; Gong, YuJing; Tang, Donghui (Frontiers in Psychology, 2019)
Purpose: The primary aim of the present study is to examine the effect of 8-week exercise intervention combined with aerobic jogging and yoga on implicit emotion regulation ability. The secondary aim is to explore the specific potential pathways by which the exercise intervention fosters implicit emotion regulation. This may help to understand how the key components of exercise intervention contribute to emotional benefits. Methods: Sixty participants were randomly allocated to one of two parallel groups: (a) the exercise intervention group (n= 29) and (b) the waitlist control group (n= 31). Participants were asked to fill out scales measuring mindfulness and instructed to complete an emotion regulation task to assess implicit emotion regulation ability as well as the PWC 170 Test to evaluate aerobic fitness before and after the exercise intervention. Results: The results of two-way repeated ANOVA revealed that 8 weeks of exercise intervention improved implicit emotion regulation, mindfulness and aerobic fitness levels. Path analysis showed that only improved aerobic fitness mediated the intervention effect on implicit emotion regulation ability, controlling for change in negative affect. Notably, the relationship between the effects on implicit emotion regulation ability and aerobic fitness was moderated by improved mindfulness. Conclusion: 8 weeks exercise intervention improves implicit emotion regulation ability. The aerobic fitness may be an essential pathway which mediates the efficacy on implicit emotion regulation ability. Furthermore different components such as aerobic fitness and mindfulness may interactively contribute to such emotional benefits.